Effect of Electronic Health Record Use on Nursing Documentation Quality and Workflow Efficiency at Nishtar Hospital Multan: A Cross-Sectional Study - Aiza Khan; Mobina Nawaz; Noor Ul Eman (Pakistan Journal of Clinical Research, 2026)
Background: The global transition from paper-based to electronic health records (EHRs) has transformed nursing documentation, offering potential improvements in documentation quality, patient safety, and workflow efficiency. However, evidence from resource-constrained settings such as Pakistan remains limited. This study evaluated the impact of EHR use on nursing documentation and workflow efficiency at Nishtar Hospital Multan. To assess the effect of EHR use on documentation quality and workflow efficiency among nurses at Nishtar Hospital Multan, Pakistan. Methods: A cross-sectional study included 320 registered nurses from inpatient, outpatient, and emergency departments. Data were collected using a validated questionnaire comprising demographic characteristics, the Nursing Documentation Quality Assessment Scale (NDQAS), and Workflow Efficiency Scale (WES). Descriptive statistics, independent t-tests, one-way ANOVA, and multiple linear regression were performed using SPSS version 27. Results: Mean documentation quality was 68.4 ± 12.7/100, indicating moderate quality, while workflow efficiency averaged 58.2 ± 14.3/100. EHR use was significantly associated with improved documentation completeness (β = 0.34, p < 0.001) and accuracy (β = 0.28, p < 0.001), but also increased documentation time (β = −0.22, p = 0.003) and perceived burden (β = −0.31, p < 0.001). Trained nurses had significantly higher documentation quality (74.6 ± 10.2 vs. 63.8 ± 13.1) and workflow efficiency (64.1 ± 12.4 vs. 53.7 ± 14.8; both p < 0.001). Major barriers included inadequate training (62.5%), technical problems (41.3%), and poor usability (38.8%). Conclusion: EHRs improve documentation completeness and accuracy but may increase documentation time and workload. Effective implementation requires comprehensive training, improved usability, technical support, and organizational support.